Glycans – the third revolution in evolution - Lauc, Gordan; Krištić, Jasminka; Zoldoš, Vlatka (Frontiers in Genetics, 2014)
The development and maintenance of a complex organism composed of trillions of cells is an extremely complex task. At the molecular level each process requires specific molecular structures to perform it, thus it is difficult to imagine how less than tenfold increase in the number of genes between simple bacteria and higher eukaryotes enabled this quantum leap in complexity. In this perspective article we present the hypothesis that the invention of glycans was the third revolution in evolution (the appearance of nucleic acids and proteins being the first two), which enabled the creation of novel molecular entities that did not require genetic template. Contrary to proteins and nucleic acids, which are made from the direct DNA template, glycans are product of a complex biosynthetic pathway affected by hundreds of genetic and environmental factors. Therefore glycans enable adaptive response to environmental changes and, unlike other epiproteomic modifications, which act as off/on switches, glycosylation significantly contributes to protein structure. The importance of glycosylation is evident from the fact that nearly all proteins invented after the appearance of multicellular life are composed of both polypeptide and glycan parts.